2018
DOI: 10.22146/jmpf.34438
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of BPJS Service Quality Level and Patient Characteristics to Patient Satisfaction in Primary Health Facilities

Abstract: ABSTRAKPelayanan kesehatan di era JKN diselenggarakan oleh semua Fasilitas Kesehatan yang bekerjasama dengan BPJS. Kepuasan pasien merupakan indikator penentu berhasil atau tidak suatu program. Kepuasan adalah perasaan senang seseorang yang berasal dari perbandingan antara suatu produk atau kinerja dengan harapannya, jika kinerja dibawah harapan maka pelanggan tidak merasa puas. Penelitian ini bertujuan untuk mengetahui pengaruh kepesertaan, pelayanan dan pembiayaan terhadap kepuasan pasien BPJS di Fasilitas K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
0
1
Order By: Relevance
“…This result is contradictory to the research by Abidin (2016) in Puskesmas Cempae Parepare City which showed that from 185 patients of BPJS Kesehatan, 129 patients or 69,73% felt satisfied with the health services in the puskesmas and 56 patients or 30,27% felt dissatisfied with the health services in the puskesmas. This result is also contradictory with the research by Marhenta et al (2018) in the First Level Health Facilities in Karanganyar Regency in 278 BPJS patients who stated that all respondents felt satisfied with the services of JKN system, however, they kept submitting complaints and suggestions for improvement.…”
Section: Discussion the Patients' Satisfaction Towards Health Service...contrasting
confidence: 72%
“…This result is contradictory to the research by Abidin (2016) in Puskesmas Cempae Parepare City which showed that from 185 patients of BPJS Kesehatan, 129 patients or 69,73% felt satisfied with the health services in the puskesmas and 56 patients or 30,27% felt dissatisfied with the health services in the puskesmas. This result is also contradictory with the research by Marhenta et al (2018) in the First Level Health Facilities in Karanganyar Regency in 278 BPJS patients who stated that all respondents felt satisfied with the services of JKN system, however, they kept submitting complaints and suggestions for improvement.…”
Section: Discussion the Patients' Satisfaction Towards Health Service...contrasting
confidence: 72%
“…Badan Penyelenggara Jaminan Sosial Kesehatan (JKN) mengelola sistem JKN yang memberikan pelayanan secara kemitraan dengan fasilitas yang ada di seluruh Indonesia. Konsep pelayanan berjenjang dikembangkan dalam sistem JKN, yaitu sistem pelayanan kesehatan dimana fasilitas kesehatan tingkat pertama memberikan pelayanan kesehatan medis dan standar kompetensinya, seperti Puskesmas, Klinik Pratama atau sejenisnya, praktik dokter, dokter gigi, dan rumah sakit kelas D (Marhenta et al, 2018).…”
Section: Pendahuluanunclassified